Technology Based RDF Waste Management For Community Empowerment and Circular Economy Strengthening In Bandung Regency - Widiya Avianti; Arini Permatasari; Dedi Suryadi; Dani Misha Krakatau (Inaba of Community Services Journal, 2025)
Waste management has become a critical environmental issue in Bandung Regency due to increasing waste generation and the limited capacity of landfill sites. Improper waste management contributes to environmental pollution, public health problems, and the underutilization of waste as a potential economic resource. This Community Service Program (PKM) aimed to strengthen community capacity and participation in technology-based waste management through collaboration with the Environmental Agency of Bandung Regency by applying Refuse Derived Fuel (RDF) technology. The program was implemented using a participatory approach, including initial socialization and education on waste management and environmental impacts, technical training on the operation and maintenance of RDF machines, and continuous assistance in managing processed waste products with economic value, such as organic compost and plastic pellets. Program evaluation employed a multidimensional impact assessment covering environmental, social, and economic aspects through pre-test and post-test instruments, participatory observation, and activity documentation. The results indicate a significant improvement in community knowledge, awareness, and participation in waste management practices, along with the potential reduction of landfill burden and the creation of new employment opportunities. This program demonstrates that technology-based waste management combined with a community-based waste management approach and circular economy principles can serve as a sustainable solution that delivers environmental, social, and economic benefits for local communities.